Edukasi Anti-Bullying Berbasis Sekolah Inklusif pada Pendidikan Dasar - Novita Budiarti; Siti Umi Latifah; Budi Santoso (Yayasan Azhar Amanaa Yogyakarta, 2026)
Bullying in primary education becomes increasingly complex in inclusive school settings because students with special educational needs, learning difficulties, and characteristics perceived as different face a greater risk of victimization and social exclusion. This study aims to analyze anti-bullying education strategies aligned with the principles of inclusive education and to formulate a conceptual framework integrating the roles of teachers, students, parents, peers, school policies, and school culture. This study employed a qualitative library research design. The data were drawn from 24 scholarly articles, including nationally accredited journal articles, international articles indexed in Scopus, and systematic reviews and meta-analyses. The data were analyzed using qualitative content analysis through coding, categorization, comparison of findings, and thematic development. The findings indicate that inclusive school-based anti-bullying education should be developed through five key components: identifying student vulnerabilities, understanding the impacts of bullying, implementing accessible and participatory educational strategies, strengthening collaboration among teachers, parents, and peers, and adopting a whole-school approach. The proposed framework is preventive, participatory, collaborative, restorative, sustainable, and responsive to the diverse needs of learners. This study underscores the importance of positioning inclusivity as a fundamental principle in designing anti-bullying policies, learning activities, reporting mechanisms, student support, case management, and program evaluation in primary education.